Human rights and civil liberties - Healey, Justin (Issues in society (Balmain, N.S.W.), 2011)
Protecting and promoting human rights requires balancing the interests of individuals and groups with the interests of society including security, public health and public order. This book examines Australia's human rights record and a range of options in the debate over adequate and appropriate human rights protection. This book presents the topic in three chapters: Human rights in Australia; Arguments for a bill of rights; and Arguments against a bill of rights.